Pengaruh Return On Assets (ROA), Return On Equity (ROE), Net Profit Margin (NPM), Dan Gross Profit Margin (GPM) Terhadap Harga Saham Perbankan Syariah Periode Tahun 2014-2018 - Nur Ahmadi Bi Rahmani (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2019)
The financial statements especially related to ROA, ROE, NPM, and GPM are one of the important information used by investors to assess the performance of the company. This research aims to find out and study the influence of ROA, ROE, NPM, and GPM variables against sharia banking share price of 2014-2018 period. The research object is a sharia bank that has published the financial statements period 2014-2018. The data used is the secondary data in the form of annual data taken from the annual report of each bank. The results of the research showing Return On Assets (Roa), Return On Equity (Roe), Net Profit Margin (NPM), and Gross Profit Margin (GPM) have a significant influence on the share price of banking companies in Indonesia